Pengaruh Pengungkapan Sustainability Reporting Terhadap Respon Investor - Swenjiadi, Jenawan (Business Accounting Review, 2015)
The study attempts to determine whether sustainability reporting disclosured by Indonesia companies affect investor response. Sustainability reporting is measured based its completeness compared to GRI 3.1 guidelines. Investors response is measured by cumulative abnormal return. Multiple linear regression was used to analyze this study. The study found sustainability reporting doesnât affect investor response